A class of hyperrings connected to preordered generalized Γ-rings. (February 2015) - Jafarpour, M.; Aghabozorgi, H.; Davvaz, B.
Abstract: In this paper, we define the notion of preordered weak Γ -rings as a generalization of the concept of Γ -rings, the basic properties of prime ideals in weak Γ -rings are developed. At the end we construct a class of hyperrings in the sense of Rota from weak Γ -rings and also a connection between morphisms of the weak Γ -rings and the morphism of associated weak Γ -hyperrings has been investigated.